Hubungan Corporate Social Responsibility dengan Earnings Quality pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2019 - Priscillia Puspita Lestari; Yie Ke Feliana (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2019)
Abstract Earnings is one of some important things that company stakeholders pay attention to in making decisions related to the company. Therefore, the quality of earnings reported by companies need to be ensured that it accurately reflects tha real conditions of the company. Besides earnings, stakeholders also pay attention to corporate social responsibility activities that has been done by company as the implementation of triple bottom line concept. This study aims to investigate the relationship between corporate social responsibility (CSR) and earnings quality reported by firms. CSR is measured by using the CSRD Index based on 91 GRI criteria, while earnings quality is proxied by accrual earnings management and measured by calculating the discretionary accruals. The research object in this study is all entities listed on the Indonesia Stock Exchange (IDX) in the period of 2016-2019. After selecting companies based on predetermined sample criteria, the totals of sample numbers in this study is 191 companies in 2016-2019. The result of this study prove that there is no significant relationship between CSR and earnings quality. Keywords: corporate social responsibility, earnings quality, earnings management